Practices of Presence: Performing Arts and Philosophical Inquiry - Alessandro Giovanni Bertinetto; Lisa Giombini (Philosophies)
Over the past few decades, performance theory has flourished into a dynamic interdisciplinary discourse, drawing insights from fields such as anthropology, sociology, linguistics, psychoanalysis, political theory, cultural studies, and feminism [...]